A theory of optimal green defaults - Georg Meran; Reimund Schwarze (Helmholtz-Zentrum für Umweltforschung (UFZ), 2015)
This paper develops an analytical framework for studying the Baumol-Oates efficiency of traditional single instrument abatementpolicies vis-à-vis green defaults in the face of price inertia and deliberate defaultingby subpopulations. In this special case ofbehavioural heterogeneity, command and control approaches can outperform price-based instruments while pure tax/subsidy schemes need tobe adjusted in order to achievepolitically desired levels of abatement. We also prove that choice-preserving nudges are superior to any single-instrument policy in this case. An average marginal abatement cost rule is developed to optimise the green defaults and traditional policies of standards and prices under different degrees of market rigidity.
Keywords: H21; H23; L51; Q52; Q58; 330